Exploring How Secondary School Principals Implement Multicultural Education in The Freedom of Learning Era - Prasetyarini, Aryati; Anif, Sofyan; Harsono, H; Narimo, Sabar (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2021)
Purpose: The program “Sekolah Penggerak” (School Activator) implemented in Indonesia in the recent years is conducted to encourage school principals in realizing an advanced Indonesia that is sovereign, independent, and has personality through the creation of Pancasila Students. One of the indicators of Pancasila Students is global diversity. This study aims to explore how two senior excellent high schools in Surakarta manage multicultural education especially on developing students’ character “global diversity” (kebhinekaan global). The schools are chosen as activators and motors of the country’s educational transformation program. Both are characterized by having students with various cultures (religion, ethnicity, gender, economic social background, and culture). Methodology: This is a qualitative study in which the researcher applied ethnography. To collect the data, the researcher interviewed the three schools’ principal, teachers, and students. In addition, the researcher observed the schools and collected documents. Results: The findings show that the schools principals plan the education character by involving teachers, staffs, and parents. To monitor the implementation, the principals assign the senior teachers to help them monitor the implementation. They also revitalize the school activities which encourage students with various background to communicate and collaborate. Evaluation and Reflection are conducted once a month.